Measure the impressions of users of smart applications for performing Umrah, prayers, and visits in the Grand Mosque and the Prophet's Mosque: Field Study - Felemban, Hanin Hasan; AbdulHamid, Hani Housni (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to measure the impressions of users of smart applications for performing Umrah, prayers, and visits in the Grand Mosque and the Prophet's Mosque. In order to achieve the objectives of the study, the descriptive and analytical approach was used, and the study sample consisted of (412) users of smart applications, and a questionnaire was designed to measure the users ’impression consisting of four main axes, the results showed: The axis (the benefit of users of smart applications in (Creating spacing) and limiting the spread of Corona disease (Covid-19) to a degree (strongly agree), in second place (the impression of users of smart applications for performing Umrah, prayers, and visits in the Grand Mosque and the Prophet's Mosque) with a degree (strongly agree), in the third place came the axis (the extent to which users of special smart applications benefit (by their performance) Umrah, prayers, and visits in the Grand Mosque and the Prophet's Mosque) with a degree (strongly agree), in the last place (Challenges of using smart applications for performing Umrah, prayers, and visiting in the Grand Mosque and the Prophet's Mosque), with a degree of (neutral). The study recommended the need to educate visitors and pilgrims about the importance and how to use the Smart applications for Umrah, pilgrimage and prayers, and the necessity to continuously develop applications based on user feedback and the results of studies to achieve the best service for visitors, and work to integrate all these applications into one application to facilitate its use, and the need for the Ministry of Hajj and Umrah to pay attention to supervising the content provided through the available interactive applications.
Keywords: smart applications; Umrah; prayers; visit